PENGARUH SHOPEEPAYLATER DAN LITERASI KEUANGAN TERHADAP PEMBELIAN IMPULSIVE PADA MAHASISWA UIN MALANG JURUSAN MANAJEMEN 2018-2020 - grahita diaza tianrauta; Mardiana, Mardiana (Universitas Islam Lamongan, 2023)
This study aims to test and determine the effect of using the shopeepaylater feature and financial literacy on the impulsive purchases of UIN Malang management students. This type of research can be classified into a type of quantitative research with a descriptive approach and the data used is secondary data. The survey method was used in this study to determine the effect of using shopee paylater on impulsive purchases of UIN Malang students majoring in management class of 2018-2021 assisted by the Smart.Pls statistical tool. The sample needed in this study was 132 respondents. This research proves that there is a positive effect of Shopeepay Later on impulse purchases. Financial Literacy can influence impulsive buying significantly. Students majoring in UIN Malang management who are based on strong knowledge and search for information about platforms, will find it easier to trust Shopeepay Later because they feel very helpful when making purchases by presenting a comfortable and worry-free nature.